(untitled) - Kovac, Bronislav; Zabka, Branislav (Doprava a spoje, 2010)
The critical issues concerning solutions, process assessment, evaluation and suggestions of precautions to eliminate the negative impacts of the noise pollutions in environment from the road transport are addressed in this contribution. Proposed measures must be in accordance with threshold level of the noise for the road traffic in the environment stated by the legislation of Slovak republic.